STABILITY OF A PREY-PREDATOR MODEL WITH SIS EPIDEMICDISEASE IN PREY - Bahlool, Dahlia (Iraqi Journal of Science, 2024)
In this paper, an eco-epidemiolo-gical model consisting of prey-predator modelwith SIS disease is proposed and analyzed. The existence and the stability analysisof all possible equilibrium points are carried out. The persistent conditions of theproposed system are established. The global dynamics of the system is studiednumerically.